2021
DOI: 10.1038/s41467-021-26408-3
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage deletion of Noc4l triggers endosomal TLR4/TRIF signal and leads to insulin resistance

Abstract: In obesity, macrophages drive a low-grade systemic inflammation (LSI) and insulin resistance (IR). The ribosome biosynthesis protein NOC4 (NOC4) mediates 40 S ribosomal subunits synthesis in yeast. Hereby, we reported an unexpected location and function of NOC4L, which was preferentially expressed in human and mouse macrophages. NOC4L was decreased in both obese human and mice. The macrophage-specific deletion of Noc4l in mice displayed IR and LSI. Conversely, Noc4l overexpression by lentivirus treatment and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…LPS is one of the upstream factors that activate NF-κB and can be specifically recognized by TLR4, triggering a molecular signaling cascade through two transduction pathways involving MyD88-dependent and non-MyD88-dependent pathways, ultimately promoting the activation status of NF-κB and regulating the expression of multiple inflammatory mediators. ,, We aimed to inquire whether DOP could inhibit the activation of NF-κB through a non-MyD88-dependent pathway. The Western blotting analysis (Figure A,B) revealed that T2DM mice had high protein expression of key molecules ( P < 0.001) in the intestinal non-MyD88-dependent pathway such as TLR4, TRAM, and TRIF, which was consistent with previous studies. , After DOP administration, the amounts of expression of these key proteins TLR4, TRAM, and TRIF were noticeably adjusted downward ( P < 0.001). In addition, the increased phosphorylation of IKKβ and NF-κB p65 occurred in the MC group mice (Figure C,D), indicating an increase in NF-κB p65 translocation from cytoplasm to nucleus, but DOP treatment blocked this effect ( P < 0.001).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…LPS is one of the upstream factors that activate NF-κB and can be specifically recognized by TLR4, triggering a molecular signaling cascade through two transduction pathways involving MyD88-dependent and non-MyD88-dependent pathways, ultimately promoting the activation status of NF-κB and regulating the expression of multiple inflammatory mediators. ,, We aimed to inquire whether DOP could inhibit the activation of NF-κB through a non-MyD88-dependent pathway. The Western blotting analysis (Figure A,B) revealed that T2DM mice had high protein expression of key molecules ( P < 0.001) in the intestinal non-MyD88-dependent pathway such as TLR4, TRAM, and TRIF, which was consistent with previous studies. , After DOP administration, the amounts of expression of these key proteins TLR4, TRAM, and TRIF were noticeably adjusted downward ( P < 0.001). In addition, the increased phosphorylation of IKKβ and NF-κB p65 occurred in the MC group mice (Figure C,D), indicating an increase in NF-κB p65 translocation from cytoplasm to nucleus, but DOP treatment blocked this effect ( P < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…The Western blotting analysis (Figure 7A,B) revealed that T2DM mice had high protein expression of key molecules (P < 0.001) in the intestinal non-MyD88dependent pathway such as TLR4, TRAM, and TRIF, which was consistent with previous studies. 43,44 After DOP administration, the amounts of expression of these key proteins TLR4, TRAM, and TRIF were noticeably adjusted downward (P < 0.001). In addition, the increased phosphorylation of IKKβ and NF-κB p65 occurred in the MC group mice (Figure 7C,D), indicating an increase in NF-κB p65 translocation from cytoplasm to nucleus, but DOP treatment blocked this effect (P < 0.001).…”
Section: Analysis Of Intestinal Tight Junction Proteins In T2dm Mice ...mentioning
confidence: 99%
“…This consequently inhibits the production of inflammatory cytokines, subsequently improving local and systemic inflammation and reducing insulin resistance. 48 Another study revealed that TLR4 knockout activated TRIF/IRF3 signaling, induced inflammation, and increased the spleen index. 49 Studies with TLR2 knockout ( Tlr2 −/− ) mice revealed other possible mechanisms leading to diabetic and obese phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Liver macrophages can produce exosomes containing insulinsensitizing miR-690 that directly inhibits de novo lipogenesis and insulin resistance in HCs through the miR-690-Nadk axis (106,107). However, the accumulation of anti-inflammatory macrophages in the liver may drive insulin resistance by increasing cytokine secretion (108,109). Additionally, KCs were found to act as central regulators in cholesterol homeostasis.…”
Section: Kupffer Cells Collaborate With Hepatocytes To Contribute To ...mentioning
confidence: 99%